SHARIAH-COMPLIANT PRICING BENCHMARK GOVERNANCE: A MAQASID-BASED ANALYSIS OF INDONIA THROUGH ABDULLAH BIN BAYYAH’S FRAMEWORK - Faiz Faiz; Ahmad Fauzi (JURNAL HAKAM, 2026)
This article examines the governance of Shariah-compliant pricing benchmarks in Indonesian Islamic finance by analyzing whether IndONIA-based pricing references can be justified through the maqāṣid al-sharī‘ah framework of Abdullah bin Bayyah. The study responds to the continuing dependence of Islamic financial institutions on conventional interest-based benchmarks, which may create risks of Shariah mimicry, reputational uncertainty, and weak public literacy regarding Islamic financial pricing. Employing a qualitative-normative method with a descriptive-analytical approach, this research analyzes regulatory documents issued by Bank Indonesia, OJK, and DSN-MUI, supported by relevant literature on Islamic legal philosophy and financial governance. The analysis is framed through Bin Bayyah’s concepts of fiqh al-wāqi‘, tashīl, i‘tibār al-ma’ālāt, and the distinction between wasīlah and ghāyah. The findings show that a pricing benchmark is not a ribawī object when it functions as a transparent valuation parameter rather than as a source of guaranteed return. In murābaḥah and ijārah contracts, the benchmark may serve as an initial pricing reference and rental adjustment indicator, while in muḍārabah and mushārakah contracts, it may only operate as an expected return or performance benchmark. This article contributes by proposing a maqāṣid-based governance model that links real-market data, Shariah supervision, transparency, and wealth protection. It argues that IndONIA-based benchmarking can strengthen Islamic financial integrity when anchored in real economic productivity, public accountability, and distributive justice.